«Análisis de la representación del imaginario social del indígena en la película ecuatoriana “A Son of Man: La maldición del tesoro de Atahualpa”» - Romero Ortega, María José (2024)
From the very beginning of cinema itself, a compelling need to portray the "other" has grown along with it. Many films that explore the representation of the indigenous "other" reveal the colonial heritage of the thinking that engenders them. At the national level, perspectives vary between portrayals that emerge from within indigenous communities and those that do so from a distant privilege. However, those that have established a broader and more global channel of visualization have been the latter. The study aims, through a descriptive-explanatory study, to analyze the social imaginary of the Ecuadorian indigenous in the Ecuadorian film "A Son of Man: The Curse of Atahualpa's Treasure", a film nominated for Best Foreign Film at the 2019 Oscar Awards. Among the proposed objectives, it is planned to identify the semiotic elements used in the construction of the social imaginary of the indigenous, in addition to characterizing the representation of otherness; with which it is planned to establish the relationship between these two categories in the aforementioned film. By means of the methodology, the cinematographic content was evaluated through the perspective of Francesco Casetti and Federico Di Chiofor the analysis of the filmic image. In addition, two observation matrices were used to characterize social imaginaries and their representations. Additionally, the expert opinion of two professionals in the area of audiovisual image analysis and semiotics was used. The results confirm the construction of racialized imaginaries that tend to pigeonhole the indigenous "other" as the savage and the one who needs the tutelage of the white ideal. The conclusion is the remarking of a deep need for the analysis of the cinematographic image for the generation of a critical conscience on the discourses poured by mass media that have implications in the organization of social life. Keywords: cinema; representation; indigenous; otherness; colonialism.